Adaptive Localization Using Machine Learning : Models, Methods, and Applications - Siemuri, Akpojoto Akporido (Vaasan yliopisto, 2026)
This dissertation investigates how machine learning (ML) techniques can enhance positioning accuracy when using low-cost sensors. Recent advances in affordable dual-frequency GNSS receivers and accessible GNSS correction services have opened new possibilities for developing accurate, mass-market location-based applications. These technologies include dual-frequency GNSS, Ultra-Wideband (UWB), Bluetooth direction finding, 5G, radar, inertial navigation systems (INS), image-based localization, and various GNSS correction services. A systematic review was conducted on the integration of ML in GNSS-related application, highlighting key trends, algorithmic performance, and associated challenges. A series of experimental studies were performed using commercial-grade GNSS re-ceivers including smartphone-based sensors-to develop cost-effective and robust positioning systems. These include: (i) a GNSS-only system enhanced with ML-based adaptive positioning (MAP), (ii) a GNSS/IMU solution utilizing Rauch-Tung Striebel (RTS) smoothing for improved accuracy in urban environments, and (iii) a seamless indoor-outdoor localization system combining GNSS, UWB, and IMU sensors. The proposed methods demonstrated competitive performance in global benchmarks, such as the Google Smartphone Decimeter Challenge. Additionally, an alternative GNSS/IMU fusion approach using factor graph optimization (FGO) is explored, achieving better performance in signal-degraded scenarios. The work also extends to space applications with the use of ML models for precise orbit determination (POD) of low-Earth-orbit (LEO) satellites, presenting polynomial regression's advantage in modeling nonlinear orbital dynamics. Furthermore, Edge AI applications are explored through the deployment of TinyML models for on-device localization, emphasizing feasibility in constrained environments while addressing energy efficiency, privacy, and real-time adaptability. Ethical implications of AI/ML in localization are examined in the context of the EU AI Act, emphasizing fairness, transparency, and responsible Al governance. Together, these contributions demonstrate the practical, scalable, and ethical use of ML and TinyML for accurate and reliable localization across diverse use cases and environments.

Tämä väitöskirja tutkii koneoppimisen (ML) tekniikoiden käyttöä paikannus-tarkkuuden parantamiseksi käyttämällä edullisia antureita. Viimeaikaiset edistysaskeleet edullisissa kaksitaajuisissa GNSS-vastaanottimissa ja edulliset GNSS-signaalinkorjauspalvelut ovat luoneet uusia mahdollisuuksia massamarkkinoiden tarkkojen sijaintiperusteisten sovellusten kehittämiselle. Mainittuihin teknologioihin kuuluvat GNSS, ultralaajakaista (UWB), Bluetooth, 5G, tutka, inertianavigointijärjestelmät (INS), näköön perustuva paikannus ja erilaiset GNSS-korjauspalvelut. Koneoppimisen hyödyntämistä GNSS-sovelluksissa tarkasteltiin systemaattisesti. Katsaukseen sisältyi sarja kokeellisia tutkimuksia kaupallisen luokan GNSS-vastaanottimilla, mukaan lukien älypuhelinpohjaisilla sensoreilla, joita käytettiin kustannustehokkaiden ja luotettavien paikannusjärjestelmien kehittämiseen. Näitä ovat: (i) pelkästään GNSS:ään perustuva järjestelmä, jota on parannettu koneoppimiseen perustuvalla adaptiivisella paikannuksella (MAP), (ii) GNSS/IMU-ratkaisu, joka hyödyntää Rauch-Tung-Striebel (RTS) -tasoitusta tarkkuuden parantamiseksi kaupunkiympäristöissä, ja (iii) saumaton sisä- ja ulkotilojen paikannusjärjestelmä, joka yhdistää GNSS-, UWB- ja IMU-anturit. Ehdotetut menetelmät osoittivat kilpailukykyistä suorituskykyä globaaleissa vertailuissa, kuten Google Smartphone Decimeter Challengessa. Lisäksi tutkitaan vaihtoehtoista GNSS/IMU-fuusiomenetelmää, joka käyttää tekijägraafioptimointia (FGO), ja jolla saavutetaan parempi suorituskyky signaalin heikkenemisen tilanteissa. Väitöskirja ulottuu myös avaruussovelluksiin käyttämällä koneoppimismalleja matalan Maan kiertoradan (LEO) satelliittien tarkkaan kiertoradan määritykseen (POD), mikä osoittaa polynomiregression edun epälineaarisen kiertoradan dynamiikan mallintamisessa. Lisäksi tutkitaan Edge AI -sovelluksia ottamalla käyttöön TinyML-malleja laitteen paikannukseen, korostaen toteutettavuutta rajoitetuissa ympäristöissä ja ottaen samalla huomioon energiatehokkuuden, yksityisyyden ja reaaliaikaisen sopeutumiskyvyn. Tekoälyn/koneoppimisen eettisiä vaikutuksia lokalisoinnissa tarkastellaan EU:n tekoälylain kontekstissa painottaen oikeudenmukaisuutta, läpinäkyvyyttä ja vastuullista tekoälyn hallintaa. Yhdessä nämä tutkimukset osoittavat koneoppimisen ja TinyML:n käytännöllisen, skaalautuvan ja eettisen käytön tarkkaan ja luotettavaan lokalisointiin erilaisissa käyttötapauksissa ja ympäristöissä.
Keywords: satellite navigation; locationing; information technology; technology; computer-assisted teaching; communications technology; machine learning; satellite navigators; fi=Tietotekniikka tekn|en=Information Technology tech|